Evaluation of Using an Octavius 4D Measuring System for Patient-Specific VMAT Quality Assurance - Yawo Atsu Constantino Fiagan; Kodjo Joël Fabrice N‘Guessan; Adama Diakité; Komlanvi Victor Adjenou; Thierry Gevaert; Dirk Verellen (Radiation)
Background: Quality assurance (QA) programs are designed to improve the quality and safety of radiation treatments, including patient-specific QA (PSQA). The objective of this study was to investigate the conditions in which pretreatment PSQA is performed, to evaluate the root cause of the implementation of more complex techniques, and to identify areas for potential improvement. Materials/Methods: The Octavius 4D (O4D) system accuracy was evaluated using an O4D homogeneous phantom for different field sizes. Tests of the system response to dose linearity, field sizes, and PDD differences were performed against calculated doses for a 6 MV photon beam. The pretreatment verification of 40 VMAT plans was performed using the PTW VeriSoft software (version 8.0.1) for local and global 3D gamma analysis. The reconstructed 3D dose was compared to the calculated dose using 2%/2 mm and 3%/3 mm, 20% of the low-dose threshold, and 95% of the gamma passing rate (%GP) tolerance level. The sensitivity of the O4D system in detecting VMAT delivery and setup errors has been investigated by measuring the variation in %GP values before and after the simulated errors. Results: The O4D system reported good agreement for linearity, field size, and PDD differences with TPS dose, being within ±2% tolerance. The output factors were consistent between the ionization chamber and the O4D detector down to a 4 × 4 cm2 field size with a maximum deviation less than 1%. The introduction of deliberate errors caused a decrease in %GP values. In most scenarios, the %GP value of the simulated errors was detected with 2%/2 mm. Conclusion: The results indicate that the O4D system is sensitive enough to detect delivery and setup errors with the restrictive global criterion of 2%/2 mm for routine pretreatment verification.